Ventilator-associated pneumonia - R Sanketh; Balaji Sankar; Jolly Chandran; Ebor Jacob G. James (Wolters Kluwer Medknow Publications, 2023)
Ventilator-associated pneumonia (VAP) has traditionally been defined as pneumonia in patients with mechanical ventilation for at least 48 h. Despite advancements in critical care, VAP remains to be a complication resulting in huge financial burden to patients. The limitations to the criteria have resulted in an urge to redefine VAP by the Centers for Disease Control and Prevention. Ventilator-associated event (VAE) has been well categorized in adult population; however, in pediatric cohort, while surveillance enhances the detection of infectious and noninfectious complications which can influence patient outcomes, there are many gaps in its classification and management. Establishing a diagnosis of VAP/VAE is crucial in management of a critically ill patient. The role of clinical criteria in concordance with laboratory evidence of inflammatory markers along with chest X-ray helps in supplementing the diagnosis. The presence of culture positivity aids in diagnosis with minimally invasive bronchoalveolar lavage providing a reasonable and safe method. Early empiric antibiotic treatment in suspected patients is beneficial. The role of antibiotic stewardship will help in prevention of antimicrobial resistance in treatment of VAP. More emphasis on VAP prevention measures with multidisciplinary approach is the way forward in overcoming this morbid condition in the intensive care units.